ISLAMIC EDUCATION AND INDOCTRINATION THE CASE IN INDONESIA: CHARLENE TAN - Yosie Kristin Pandriyani; Hodiqotul Atfaliyah; B.Syafuri; Apud (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2026)
This study examines the practice of Islamic education and the issue of indoctrination in the context of Indonesian education, based on the perspective of Charlene Tan. The study aims to analyze how Islamic values ??are transmitted in the educational process and to distinguish between educational practices that are educationally educative and indoctrinating. The research approach used is a qualitative case study method, through analysis of curriculum documents, educational policies, and academic literature relevant to Islamic education in Indonesia. The study's findings indicate that Islamic education in Indonesia is not entirely indoctrinating, but rather combines the strengthening of religious values ??with the development of students' critical thinking skills. However, in certain practices, a pedagogical tendency toward normative doctrinal instillation remains. This study emphasizes the importance of a dialogical, reflective, and contextual approach to Islamic education to align with modern educational principles and democratic values